PROFITABILITAS DAN LIKUIDITAS TERHADAP AGRESIVITAS PAJAK DENGAN CAPITAL INTENSITY SEBAGAI MODERATING - Arwa El Zahra; Zuraidah (RISTANSI: Riset Akuntansi, 2025)
This  research  endeavor  seeks  to  delve  into  two  pivotal  aspects:  initially,  it  seeks  to  assess  how  profitability  and  liquidity  correlate  with  tax agressiveness,  and  secondarily,  it  aims  to  explore  the  mediating  influence  of  capital  intensity  on  the  interplay  between  profitability,  liquidity,  and  tax agressiveness.  The  study  centers  on  the  mining  firms  listed  on  the  IDX,  harnessing  their  financial  records  from  2014  to  2023  as  the  cornerstone  for  data  analysis.  Through  a  strategic  sampling  method,  a  subset  of  10  companies  was  identified  for  the  study.  The  analytical  tools  employed  were  multiple  linear  regression  and  multivariate  regression  analysis,  executed  via  Eviews  12  software.  The  findings  indicate  that  profitability  has  a  notable  impact  on  tax  agressiveness,  whereas  liquidity  shows  a  detrimental,  albeit  non-statistically  significant,  effect.  Notably,  capital  intensity  does  not  serve  as  a  mitigating  factor  in  the  relationship  between  profitability,  liquidity,  and  tax  agressiveness.